PELAKSANAAN PIK-REMAJA (PUSAT INFORMASI KONSELING REMAJA) DI SMA/SMK SE KOTA PEKANBARU - Fenny Siti Rubia Harahap, Een husanah, (Menara Ilmu, 2019)
Teenagers have problems very complex and tend to behave unhealthy life whereyouth and sexual urge is two things that is deeply connected.In addition the curiosity aboutsexual teenagers high often get teens want to practice directly to obtain what she wanted toknow about sexual.Pik-remaja ( center of information and counseling teenagers ) is acontainer activities in governance of, by and for young people in the reproductive healthteenagers, which one its aims to provide information adolescent reproductive health ( KRR), improve understanding, the attitudes and behavior positive teenagers.This study attemptsto understand the implementation of the pik-remaja ( center of information and counselingteenagers ) in high school and vocational se the city of pekanbaru 2015.The research isresearch descriptive quantitative, technique the sample collection in total of sampling withdata analysis univariat.The results of the study obtained the majority of the implementationof the PIK- Teenagers.Keyword : Implementation Information And Counseling Center, SMA/ SMK TheWhole Town Pekanbaru